Konstrukcija napajalnika za visokovakuumski merilnik s hladno katodo - Grašič, Igor (Kovine zlitine tehnologije, 1998)
While developing the high vacuum gauge with cold catode we met with the problem of supplying the gauge head with high voltage and measuring a low current at high voltage. A power supply should be small as possible, have special characteristics enabling long term short circuit operation and act like an ideal voltage source with appreciable resistance. The transformation of nonlinear ratio between the real presssure in the system and the measured ion current i=f(p) in the gauge head should be provided. Elements under high voltage and/or high vacuum represent a special care. The article describes the construction and realization of such a power supply.
Keywords: merjenje; merilniki; vakuum; zgradba; karakteristike